TLR2 and TLR4 Expression and Inflammatory Cytokines are Altered in the Airway Epithelium of Those with Alcohol Use Disorders. (24th July 2015) - Bailey, Kristina L.; Romberger, Debra J.; Katafiasz, Dawn M.; Heires, Art J.; Sisson, Joseph H.; Wyatt, Todd A.; Burnham, Ellen L.
<x xml:space="preserve">Abstract</x> Background The lung has a highly regulated system of innate immunity to protect itself from inhaled microbes and toxins. The first line of defense is mucociliary clearance, but if invaders overcome this, inflammatory pathways are activated. Toll‐like receptors (TLRs) are expressed on the airway epithelium. Their signaling initiates the inflammatory cascade and leads to production of inflammatory cytokines such as interleukin (IL)‐6 and IL‐8. We hypothesized that airway epithelial insults, including heavy alcohol intake or smoking, would alter the expression of TLRs on the airway epithelium. Methods Bronchoscopy with bronchoalveolar lavage and brushings of the airway epithelium was performed in otherwise healthy subjects who had normal chest radiographs and spirometry. A history of alcohol use disorders (AUDs) was ascertained using the Alcohol Use Disorders Identification Test (AUDIT), and a history of cigarette smoking was also obtained. Age, gender, and nutritional status in all groups were similar. We used real‐time polymerase chain reaction (PCR) to quantitate TLR1 to 9 and enzyme‐linked immune assay to measure tumor necrosis factor‐α, IL‐6, and IL‐8. Results Airway brushings were obtained from 26 nonsmoking/non‐AUD subjects, 28 smoking/non‐AUD subjects, 36 smoking/AUD subjects, and 17 nonsmoking/AUD subjects. We found that TLR2 is up‐regulated in AUD subjects, compared to nonsmoking/non‐AUD subjects, and correlated with their AUDIT scores. We also measured a decrease in TLR4 expression in AUD subjects that correlated with AUDIT score. IL‐6 and IL‐8 were also increased in bronchial washings from AUD subjects. Conclusions We have previously demonstrated in normal human bronchial epithelial cells that in vitro alcohol exposure up‐regulates TLR2 through a NO/cGMP/PKG‐dependent pathway, resulting in up‐regulation of inflammatory cytokine production after Gram‐positive bacterial product stimulation. Our current translational study confirms that TLR2 is also up‐regulated in humans with AUDs.